Textured vegetable protein from flaxseed press cake and pea – syntonizing chemical and structural properties - Luise Lallinger; Cornelia Rauh (Future Foods)
Flaxseed press cake (FS) was mixed with pea protein isolate and low-moisture twin-screw-extruded to valorize the oil production side stream as meat analogue. Water input, FS content, barrel temperature, and throughput were varied in a Box-Behnken design to test these factors’ influences on extrusion response parameters (pressure, temperature, mechanical energy input), lipid oxidation product and process contaminant formation (by liquid chromatography and head-space gas chromatography mass spectrometry), and mechanical properties of the TVPs.The water input was identified as the strongest influencing factor, reducing shear forces in the extruder and thereby reducing mechanical energy input, pressure, and temperature and affecting several TVP properties. Volatile lipid oxidation products from enzymatic oxidation in the raw materials are decomposed and steam-stripped during extrusion. Higher melt temperatures and lower water contents enhance this effect and promote the formation of masking “roasted” flavour compounds. However, acrylamide (<100 µg/kg) and trans-fatty acids (<0.4 g/kg) are also formed under flavour-improving conditions and TVP hardness is reduced. FS increases TVP density and reduces expansion and hardness. Reconciling mitigation of undesired chemical compounds and meat-like mechanical properties (at 16–18 % water, 55–65 % FS, mass flows <8 kg/h), a FS-based TVP can be created, combining nutritional and sustainability benefits of FS.